Evaluating the iron nutritional status of female university students - Fujimori, Elizabeth; Salum, Maria Josefina Leuba; Shima, Hisako (Revista da Escola de Enfermagem da USP, 1987)
A study to evaluate the iron nutritional status was carried out envolving 47 female university students, whose diets contained the average of 72% of the recommented dietary allowances of iron. The results show that, in spite of the low consumption of iron, the concentration of hemoglobin and the value of hematocrit was within the border line of normality. The possibility of the organic iron stores being minimal or absent is discussed.